Pemanfaatan Refugia Terhadap Keanekaragaman Serangga Musuh Alami Di Pertanaman Bawang Merah (Allium Cepa) - Sari, Putri Mustika; Rasyidina, Ayu; Agustinur, Agustinur; Chairudin, Chairudin; Lisa, Oviana (Jurnal Agrotek Lestari, 2024)
Refugia plants are able to control pest insects in cultivation plants, the benefits of refugia plants can become microhabibtat natural enemies. This research was conducted to see the diversity of natural enemy insects in the planting of shallots (allium cepa) by utilizing various flowering plants as edge plants. This research was conducted in the Teuku Umar University Experimental Garden. The research began in October-December 2023. This study used a non-factorial plot split plot design method with 5 levels and 4 treatments, namely: T0 = without refugia plants, T1 = Zinnia Elegans, T2 = Marigold Plants, T3 = Cosmos Plant, T4 = Zinnia elegans + marigold + cosmos. The results showed that insect identification there were 7 types of orders and 20 species of insect species. The result of the natural enemy diversity index value with the calculation of H 'data in all treatments is moderate. The results of the independence index of the type with the highest value are in the combination treatment reaching the E'1 value, which means according to E => 0.6 the level of compliance of the type is classified as high. In the yield of shallots for the highest lime weight, there is a combination of 1.890 kg.Keywords: Refugia, natural enemies, diversity, types of evenness